1985
DOI: 10.1530/acta.0.1100140
|View full text |Cite
|
Sign up to set email alerts
|

Serum thymidine activity and insulin-like growth factors in the neonatal period

Abstract: Abstract. Growth-promoting activity measured as [3H] thymidine incorporation into lectin-activated lymphocytes was determined simultaneously with radioimmunoassayable IGF I and IGF II in cord and capillary blood collected from human neonates 30 min and 24 h after birth. All the parameters studied in cord blood were lower than in normal adults. During the early postnatal period, IGF I decreased and IGF II remained unchanged, but thymidine activity increased above the normal adult level. The differences between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Our finding of low levels of IGF-I in newborns compared to adults are in agreement with previous reports by us [9] and others [26]. The findings of increased levels of IGF-I in cord serum from infants of diabetic mothers is of interest.…”
Section: Effects Of Pregnancy and Diabetes On Igf-h Levelssupporting
confidence: 93%
“…Our finding of low levels of IGF-I in newborns compared to adults are in agreement with previous reports by us [9] and others [26]. The findings of increased levels of IGF-I in cord serum from infants of diabetic mothers is of interest.…”
Section: Effects Of Pregnancy and Diabetes On Igf-h Levelssupporting
confidence: 93%
“…Liver and serum IGF-I in fetal rats correlated with fetal weight in growth retardation produced by uterine artery ligation (35). Recent studies have shown divergence patterns of thymidine uptake stimulating activity from immunoassable IGF-I concentration in blood of human fetuses at gestational ages from 2 1-28 wk (36) and cord blood of human neonates (37) suggesting that factors other than IGF contributing to thymidine activity may also play a role in fetal growth.…”
Section: Discussionmentioning
confidence: 99%
“…In order to avoid possible confounders in assessing hormone levels at birth, we took blood samples from the neonates on the 2 nd day of life and did not use cord blood in which hormone levels may derive from the maternal circulation or from other maternal tissues, such as the placenta [22,23]. …”
Section: Methodsmentioning
confidence: 99%